Empirical Determinants of Good Institutions: Do We Know Anything? - Stéphane Straub (Inter-American Development Bank, Research Department, 2000)
Abundant empirical evidence links well-functioning institutions and good governance to better economic and social outcomes. It is thus an important challenge to determine which conjunction of factors produces better institutions. Along this line, the objective of this paper is twofold. First, it examines the existing results of the literature on this matter in a critical way, tries to assess their robustness, and explores alternative methodology. Second, it makes use of a more comprehensive database, including all the aspects previously analyzed in a separate manner, to derive systematic empirical results. After discussing the traditional robustness checks employed, for example, in the empirical growth literature, which appear to be of limited usefulness, we introduce factor analysis as a preliminary step toward model specification and subsequently perform multiple regression analysis. Of the four levels of explanation that we identify, namely control and historical variables, the nature of the political game, the size and nature of existing rents to be allocated, and the nature and quality of bureaucratic incentives, the later appears to be the more clearly linked to institutional quality. However, the results prove not robust when dealing with endogeneity problems. Various kinds of interactions and non-linear effects are also investigated, yielding no clear insights. We conclude regarding the fragility of existing data, in particular with respect to the incentive structure, and the need for a better theoretical understanding of the underlying mechanisms.
Keywords: 330; Institutionelle Infrastruktur; Institutionalismus; Wirtschaftliche Effizienz; Schätzung; Welt; Governance-Ansatz